Islamic Education Based on Local Wisdom in Facing Religious Radicalism in Baubau City Islamic Boarding Schools - La Ode Bunga Ali; Musliem , Malik Al-asadii (Journal of Asian Wisdom and Islamic Behavior, 2024)
Religious radicalism is a serious threat to social harmony and national unity, including in Islamic boarding schools. This study aims to identify how local wisdom-based Islamic education can be used to prevent religious radicalism in Islamic boarding schools in Baubau City. The main problem raised is how local wisdom, which includes cultural values of tolerance, mutual cooperation, and togetherness, can be integrated into Islamic education to form moderate and anti-radicalism attitudes among students. The research method used is qualitative with a case study approach. Data were obtained through in-depth interviews, participatory observation, and document analysis at several Islamic boarding schools in Baubau City. The results of the study show that Islamic boarding schools that integrate local wisdom into their curriculum are able to create a more inclusive and tolerant educational environment. Local wisdom-based teaching has succeeded in instilling the values of moderation and diversity in students, which are important foundations in countering religious radicalism. In conclusion, Islamic education that strengthens local wisdom has a significant role in forming the character of moderate students, so that they are effective in facing the challenges of religious radicalism in the modern era.